High elevation bird communities in the Swiss Alps exhibit reduced fecundity and lifespan independently of phylogenetic effects - García-Navas, Vicente; Sattler, Thomas; Schmid, Hans; Ozgul, Arpat (Biodiversity and conservation, 2021)
The merging of community ecology and phylogenetic biology allows us to link broader evolutionary processes to local ecological processes, thereby increasing our understanding of community assembly. A recurrent way to test how species assemblages respond to different abiotic conditions and evaluate the role of evolutionary constraints in community assembly is through using environmental gradients as natural treatments. Here, we combine phylogenetic and trait-based methods to evaluate how the phylogenetic diversity and composition of bird assemblages and their community-weighted traits vary along an elevational gradient in the Swiss Alps. For this purpose, we used four life-history traits considered to be key indicators of individual species response to environmental changes: clutch size, number of breeding attempts, dispersal capacity and lifespan. Controlling for phylogeny, we determined whether environmental filters (elevation, habitat type) act on these traits independently of the level of relatedness among species. We found that phylogenetic dispersion decreases with elevation, but the signature of phylogenetic clustering was weak. Phylogenetic fuzzy weighting showed that the distribution of bird species across plots was related to the two environmental gradients; nonetheless, such influence was not determined by the phylogenetic relationships in either case. That is, there are no specific clades associated with particular elevation or habitat types. We also found that high elevation communities around the treeline were composed of species with lower reproductive rates, reduced lifespan, and lower dispersal capacity, which would make them less resilient to environmental change. Although traits showed moderate phylogenetic signal, only the lifespan was phylogenetically structured. In the remaining cases, the trait-environment association was not mediated by the phylogenetic relationships among taxa. Our study indicates that evolutionary constraints do not represent a significant driver of community assembly in Alpine bird communities and support the notion that phylogeny may often not be a good proxy for traits subject to environmental filtering.